Contested norms in fragmented institutions: Gender equality in South Africa's development cooperation. (July 2019) - Cold-Ravnkilde, Signe Marie
Engaging with gender equality norms is increasingly becoming a prerequisite for being considered a legitimate partner in international development cooperation. South Africa has often been acknowledged as having one of the world's most progressive constitutions for promoting gender equality. However, gender equality norms are heavily contested in the national political context. Situated in the gap between policy and implementation, this article explores how South Africa engages with gender equality norms as a leading actor in South–South Cooperation. It argues that contestations in competing normative environments and organizational restructuring processes are impeding the push for a policy guiding gender equality work in South Africa's development cooperation.